Use of BIM with Modular Construction in Future Construction Techniques - Ali Ünay; Asena Soyluk; İlayda Omurtay (MANAS: Journal of Engineering)
Modular construction technology and applications are rapidly evolving. Modular construction is a process in which entire rooms or sections of rooms are built in a factory setting along with electrical, mechanical, and plumbing work and then transported to a final site for assembly. With modular construction, a building is built off-site, under controlled facility conditions, with the same materials and to the same codes and standards as conventionally built facilities, but in half the time. The modular construction method is used to build various types of buildings (whether they are apartment houses, office buildings, or hotels). This construction method is used for both permanent and relocatable projects. These projects can be built with two types of modules. These are 2D panels or 3D modules. These can be combined to form a third type, hybrid modular construction. Each has its advantages. 2D panels offer easy logistics and flexibility in building design and are mounted on site. Factory productivity is increased by using 3D volumetric solutions. They only need to be installed once they are delivered. The hybrid modular structure has the advantages of the previous two. With the recent development of Building Information Modeling (BIM), the use of modular construction methods in conjunction with BIM becomes more common. As with any method, this one has advantages as well as disadvantages. Disadvantages of this method, such as a higher number of complex decisions, front-loaded design, etc., can be solved with BIM. Furthermore, the BIM platform can resolve the disadvantages of traditional construction methods, such as the difficulty of pre-project planning and coordination among members of interdisciplinary professions. With BIM and the modular construction method, physical conflicts between the structural system and its mechanical, electrical, and plumbing systems can be easily identified early in the design process, and resolution can be expedited. This article includes general information about the modular construction method, future application scenarios, use, and advantages of BIM. The document analysis method, one of the qualitative methods, was used, and in the light of the data obtained, comments and scenarios were tried to be created about the future of BIM and modular construction techniques. What distinguishes this study is that the concept of quality is examined in detail by using these two methods together.